Synthesis of Polyethylene‐Grafted Phosphite Antioxidant and Its Antioxidant Behavior in Polypropylene. Issue 7 (10th March 2020) - Zhang, Yin; Li, Huayi; Luo, Zhi; Li, Mengru; Liu, Tingting; Liu, Weiwei; Li, Qian; Hu, Youliang
Abstract: A novel macromolecular auxiliary antioxidant with polyethylene (PE) as polymer skeleton and phosphites as side groups is prepared based on commercial ethylene‐vinyl acetate (EVA) copolymers and its potential as polyolefin stabilizers is studied in depth. The synthesis approach of this PE‐grafted antioxidant consists of a typical EVA hydrolysis reaction and a two‐step nucleophilic substitution reaction of PCl3, 2, 4‐di‐tert‐butylphenol, and the hydrolysis product. Results of the thermogravimetric analysis show that the macromolecular structures endow the as‐synthesized antioxidant with much better thermal stability than that of the commercial antioxidant 168. In addition, antioxidant behaviors of the PE‐grafted antioxidants in polypropylene (PP) matrix are investigated in detail through characterization of the melt flow index of multiple‐extruded stabilized PP as well as the short‐term oxidation induction time test and the long‐term thermo‐oxidative aging test. Results show that even with extremely low content of the effective antioxidant groups, the as‐synthesized macromolecular antioxidant still has excellent antioxygenic properties. Abstract : Novel macromolecular antioxidants are synthesized via two‐step nucleophilic substitution reaction based on hydroxylated polyethylene prepared by hydrolysis of an acetate copolymer. Their thermal stability and antioxidant efficiency are better than those of antioxidant 168 evaluated in polypropylene. This kind of macromolecular auxiliary antioxidant with polyethylene backbone is expected to exhibit good volatilization and migration resistance and good compatibility with polyolefin.